2014
DOI: 10.1111/ijcp.12419
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic inertia in hypercholesterolaemia is associated with ischaemic events in primary care patients. A case-control study

Abstract: The TI in high-risk hypercholesterolaemic patients in primary prevention in Spanish primary care centres doubled the risk of an ischaemic event in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…En el caso de los centros hospitalarios, la mayoría estaban organizados en Servicios o Unidades (el 74,48%), con una media de 12,83 (11,(8)(9)(10)(11)(12)(13),87) cardiólogos de plantilla y 4,76 (4,08-5,43) médicos internos residentes en cardiología por Servicio. En la tabla 1 se muestra la distribución de participantes por comunidades autónomas.…”
Section: Resultados Descripción De La Muestra De Médicos Participantesunclassified
“…En el caso de los centros hospitalarios, la mayoría estaban organizados en Servicios o Unidades (el 74,48%), con una media de 12,83 (11,(8)(9)(10)(11)(12)(13),87) cardiólogos de plantilla y 4,76 (4,08-5,43) médicos internos residentes en cardiología por Servicio. En la tabla 1 se muestra la distribución de participantes por comunidades autónomas.…”
Section: Resultados Descripción De La Muestra De Médicos Participantesunclassified
“…Unfortunately, the under treatment of hypercholesterolemia in Europe (generally) and France (specifically) has been demonstrated in multiple previous studies [ 8 , 10–12 , 26–30 ]. The Europe-wide DA VINCI study of primary or secondary prevention patients being treated in primary care or by a cardiologist found that only 33% of patients achieved the 2019 guideline recommended LDL-C targets [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only 18% of patients in the very high-risk category achieved the 2019 LDL-C targets in the DA VINCI study; only 11% reached this target on statin monotherapy and 21% achieved the target on the combination of a statin with ezetimibe or PCSK9 inhibitor [ 29 ]. This is concerning because data show that therapeutic inertia in the management of hypercholesterolemia is associated with an increased risk of CV events [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic inertia has been shown to correlate with negative outcomes. In a case-controlled multivariate analysis of data from high-risk patients with hypercholesterolemia who had experienced an ischemic event (N = 470), therapeutic inertia at baseline was significantly associated with short-term recurrence of ischemic events (OR 2.18 [95% CI 1.04-4.51], p < 0.05) [43]. Moreover, in a retrospective database study of patients who had a cardiovascular event between 2004 and 2016 (N = 28,625), less than 25% of patients had experienced lipid control and only 22% of patients were taking a high-intensity statin 6 months after the index event [15].…”
Section: Therapeutic Inertiamentioning
confidence: 99%